Eskatologien i tidlig romersk kejsertid - Mathiassen, Svend Erik (Religionsvidenskabeligt Tidsskrift, 1987)
The so-called Messianic thought in Virgil has often been a matter of discussion. This article stresses certain aspects of this thought, namely its eschatological and soteriological implications: The primitivistic conception of the remote past as a Golden Age, exhibited in a majority of writers in classical antiquity since Hesiod, runs forth to the time of early imperial Rome. By the Augustan poets, however, especially Virgil and Horace, the idea of world-ages is presented in a new version. Virgil claims the reappearance of the Golden Age and Augustus, whose reign in the Aeneid is closely connected with the myth of Saturn as a culture-hero, is regarded as a savior, who rescued the Roman citizens from the plague of civil wars. Moreover, as asserted by Virgil, the cyclic recurrence of world-ages has come to an end. This idea must be considered as the fulfillment of an eschatology and thus, from a typological point of view, as fundamentally identical with the corresponding Christian conception of the eschatology as a present state.